Thyroid function in abnormal uterine bleeding - Kundoor, Ruthvika; Rani, Burri Sandhya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: AUB is any abnormal uterine bleeding in the absence of any palpable pelvic pathology and demonstrable extra genital causes. AUB is responsible for 10% of gynaecological complaints. Thyroid hormone is very important to affect the menstrual pattern. The objective of this study was to evaluate thyroid function test in women with AUB and to assess the menstrual pattern in women with thyroid dysfunction. Methods: The present study was conducted in the Department of Obstetrics and Gynecology, Laxmi Narasimha Hospital, Hanamkonda, Hyderabad, Telangana, India 80 women of reproductive age group between 15-45 years women with menstrual disorders like menorrhagia, oligomenorrhea, hypomenorrhea, polymenorrhea, metrorrhagia, and amenorrhea. Quantitative determination of T3, T4, and TSH by CLIA estimated in autoanlyser. Results: About 80 women participated in the study in which Most of the subjects belong to 26-30 years of age group. Maximum patients i.e. 41 (51.2%) patients were para one to 2. Commonest cause bleeding pattern was menorrhagia 41.25%. 15 apparently normal patients with AUB belonged to the category of subclinical hypothyroidism (15%). Hormonal levels revealing profound hypothyroidism in patients without any symptoms was present in only 10% of cases. 2.5% of cases had hyperthyroidism though they were clinically normal. Patients who were sub-clinically hypothyroid were maximally presenting as polymenorrhoea (50%) and menorrhagia (12.1%) and only 6.27% of patients had oligomenorrhoea. Patients who were profound hypothyroid were predominantly having polymenorrhagia (83.3%) and (62.5%) of patients had oligomenorrhoea. Conclusions: So, biochemical evaluation of thyroid functioning should be made mandatory in all provisionally diagnosed cases of AUB to detect thyroid dysfunction.